Pollen Morphology of Some Taxa of Rosaceae from Garhwal Himalaya - I - Tiwari, Prabhawati; Gloch, Eja; Bagri, Ajendra Singh; Ahmed, Fiaz; Rawat, Dinesh Singh (Indian Forester, 2022)
Palynological investigation of a particular taxonomic group helps in classification, identification and delimitation of its taxa. The present study deals with pollen morphology of 19 species of Rosaceae of Garhwal Himalaya, Uttarakhand, India. The measurements and observations of grains were made through light microscopy and scanning electron microscopy. Pollen grains of studied species were isopolar, monad and radially symmetric with tricolporate aperture. Pollen shapes varied from prolate or sub-prolate to spheroidal. In the majority of species, amb was elliptical in equatorial view with obtuse to acute end at poles and triangular in polar view. The highest and lowest polar axis lengths were recorded for Pyrus communis (46 Â± 1.6 Î¼ m) and Potentilla indica (20.1 Â± 0.7 Î¼ m) respectively. The average polar/equatorial diameter ratio (P/E ratio) was 1.4 Î¼m which ranged between 1.1 Î¼ m (Fragaria nubicola) to 1.7 Î¼ m (Chaenomeles japonica). The studied taxa were grouped into four pollen types (categories) on the basis of exine ornamentation, viz. straite, straito-perforate, straito-reticulate and straito-verrucate. The study revealed that the morphological characteristics of pollen provide significant information to categorize various taxa.